(untitled) (European Journal of Pure and Applied Mathematics, 2012)
In this work, in three dimensional Euclidean space \>E^3,\>byusing the ruled Bonnet surfaces which have been known up to now, the problem of finding some pairs of orthogonal ruled surfaces is examined and only one pair of orthogonal ruled surfaces can be obtained.